Ifenprodil for the treatment of methamphetamine use disorder: An exploratory, randomized, double‐blind, placebo‐controlled trial - Hiroko Kotajima‐Murakami; Ayumi Takano; Shinya Hirakawa; Yasukazu Ogai; Daisuke Funada; Yuko Tanibuchi; Eriko Ban; Minako Kikuchi; Hisateru Tachimori; Kazushi Maruo; Takahiro Kawashima; Yui Tomo; et al. (Wiley, 2022)
Abstract Aim No effective pharmacological interventions have been developed for patients with methamphetamine use disorder. Ifenprodil is a blocker of G protein‐activated inwardly rectifying potassium channels, which play a key role in the mechanism of action of addictive substances. We conducted a randomized, double‑blind, exploratory, dose‐ranging, placebo‐controlled trial to examine the clinical efficacy of ifenprodil for the treatment of methamphetamine use disorder. Methods Participants were assigned to three groups: placebo, 60 mg/d ifenprodil, or 120 mg/d ifenprodil. The drug administration period was 84 days. The primary outcome was the use or nonuse of methamphetamine during the drug administration period in the placebo group vs 120 mg/d ifenprodil group. We also assessed drug use status, relapse risk based on the Stimulant Relapse Risk Scale (SRRS), drug craving, and methamphetamine in urine as secondary outcomes. We further evaluated drug use status and SRRS subscale scores in patients who were not taking addiction medications during the study. Results Ifenprodil did not affect the primary or secondary outcomes. However, the additional analyses showed that the number of days of methamphetamine use during the follow‐up period and scores on the emotionality problems subscale of the SRRS improved in the 120 mg/d ifenprodil group. The safety of ifenprodil was confirmed in patients with methamphetamine use disorder. Conclusion The present findings did not confirm the efficacy of ifenprodil for methamphetamine use disorder treatment based on the primary or secondary outcomes, but we found evidence of its safety and efficacy in reducing emotionality problems. Clinical trial registration The study was registered at the University Hospital Medical Information Network Clinical Trial Registry (no. UMIN000030849) and Japan Registry of Clinical Trials (no. jRCTs031180080). The main registration site is jRCT (https://jrct.niph.go.jp/).